Bistable Retinal Schiff Base Photodynamics of Histidine Kinase Rhodopsin HKR1 from Chlamydomonas reinhardtii. (8th March 2014) - Penzkofer, Alfons; Luck, Meike; Mathes, Tilo; Hegemann, Peter
Abstract The photodynamics of the recombinant rhodopsin fragment of the histidine kinase rhodopsin HKR1 from Chlamydomonas reinhardtii was studied by absorption and fluorescence spectroscopy. The retinal cofactor of HKR1 exists in two Schiff base forms RetA and RetB. RetA is the deprotonated 13‐cis‐retinal Schiff base (RSB) absorbing in the UVA spectral region. RetB is the protonated all‐trans RSB absorbing in the blue spectral region. Blue light exposure converts RetB fully to RetA. UVA light exposure converts RetA to RetB and RetB to RetA giving a mixture determined by their absorption cross sections and their conversion efficiencies. The quantum efficiencies of conversion of RetA to RetB and RetB to RetA were determined to be 0.096 ± 0.005 and 0.405 ± 0.01 respectively. In the dark thermal equilibration between RetA and RetB with dominant RetA content occurred with a time constant of about 3 days at room temperature. The fluorescence emission behavior of RetA and RetB was studied, and fluorescence quantum yields of ϕF(RetA) = 0.00117 and ϕF(RetB) = 9.4 × 10−5 were determined. Reaction coordinate schemes of the photodynamics are developed.